2022
DOI: 10.1002/aur.2762
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of sensory modulation by age and sex in young people on the autism spectrum

Abstract: Sensory modulation symptoms form a diagnostic criterion for autism spectrum disorder and are associated with significant daily functional limitations. Utilizing caregiver report on Short Sensory Profile‐2 (SSP‐2) for 919 autistic children (3–14.11 years), we examined the expression of sensory modulation symptoms by age and sex and investigated the existence of specific sensory modulation subtypes. Sensory modulation symptoms appeared to peak in frequency during middle childhood, particularly in sensory sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…This hyper‐sensitivity profile was previously associated with the severity of expressive language deficit (Rossow et al, 2022) but also with early stages of their developmental trajectory (Ben‐Sasson et al, 2019; Green et al, 2012)—as we reported both in the PARIS and the LEAP samples. In our study, we reported a significant positive interaction (i.e., in favor of hyper‐sensitivity) between dSSP score and chronological age of the participants, which is coherent with the literature (Lane et al, 2022), with a dSSP score stability across child development described by repeated measures on the PARIS study. Although the sensory differences appear early in the development, the dSSP stability appears as a good biomarker candidate of autism spectrum (Aronson & Ferner, 2017; Baranek et al, 2013; Estes et al, 2015; O Miguel et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…This hyper‐sensitivity profile was previously associated with the severity of expressive language deficit (Rossow et al, 2022) but also with early stages of their developmental trajectory (Ben‐Sasson et al, 2019; Green et al, 2012)—as we reported both in the PARIS and the LEAP samples. In our study, we reported a significant positive interaction (i.e., in favor of hyper‐sensitivity) between dSSP score and chronological age of the participants, which is coherent with the literature (Lane et al, 2022), with a dSSP score stability across child development described by repeated measures on the PARIS study. Although the sensory differences appear early in the development, the dSSP stability appears as a good biomarker candidate of autism spectrum (Aronson & Ferner, 2017; Baranek et al, 2013; Estes et al, 2015; O Miguel et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Notably, these response patterns are not mutually exclusive, and many individuals express behaviors characteristic of multiple sensory response patterns, even within the same modality. Sensory reactivity differences are extremely common in autistic individuals: the point prevalence of a child displaying differences in any of the three response patterns (i.e., HYPER, HYPO, or SEEK in any modality) was recently estimated to be 74% using large-scale population-based data from the Autism and Developmental Disabilities Monitoring Network (18), and 70.9-88.3% of autistic youth in two large samples (from the United States and Australia, respectively) were determined to have sensory reactivity differences of at least "mild" severity (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…One issue is training dentists to distinguish the different spectra of ASD, i.e., whether classical autism or Asperger syndrome (299.00 DSM-IV), atypical autism (pervasive developmental disorder not otherwise specified, 299.80 DSM-IV), or Rett syndrome or more simply a non-autistic cognitive disorder ( 62 ). In addition, awareness of the existence of specific sensory modulation subtypes in autistic children, by sex and age, is crucial to address these patients appropriately ( 63 ).…”
Section: Oral Health Prevention In the Autistic Subject As Early As P...mentioning
confidence: 99%